Application of Electronic Nose to Discriminate Species of Mold Strains in Synthetic Brines - Sánchez, Ramiro; Pérez-Nevado, Francisco; Montero-Fernández, Ismael; Lozano, Jesús; Meléndez, Félix; Martín-Vertedor, Daniel (Frontiers in Microbiology, 2022)
The chemical composition of the brine for Spanish-style table olives plays a crucial role during the fermentation process. Traditional laboratory analysis requires a high consumption of reagents, highly qualified personnel, sophisticated equipment, long analysis times and large amounts of samples. Analysis carried out using an electronic nose (E-nose) offers an alternative, non-destructive technique and is useful in determining alterations in brines caused by microorganisms. In the present research, nine mold strains isolated from spoiled olives were inoculated in synthetic brines to determine the effect of microbial development on sensory quality, volatile profile and E-nose analysis. The brines inoculated with the mold strains presented negative attributes related to aromas of mold, wood, leather, rancidity and chemicals, among others. The highest intensity of defect was presented by the brines inoculated with the strains G.G.2, P.E.3, A.F.9 and A.F.18. A total of 19 volatile compounds were identified. Sensory analysis identified the same mold strains that contributed the most to the unpleasant brine odor. The E-nose data were able to classify the inoculated brines into different categories regardless of the intensity of the defect. The Principal Component Analysis (PCA) showed that 95.2% of the total variance was explained. These results demonstrate the capacity of the E-nose to discriminate alterations in brines produced by molds, thereby making it a useful tool to be applied during the elaboration process to detect early alterations in table olive fermentation.